Interaction behaviour of acetonitrile in the presence of acetylacetone: FTIR studies and DFT calculations. (3rd September 2022) - Dineshkumar, P.; Sahana, R.; Rajmohan, G.; Elangovan, A.; Naganandhini, S. P.; Sangeetha, T.; Arivazhagan, G.
ABSTRACT: FTIR spectral signatures of acetonitrile (AN), acetylacetone (AcAc) and their binary solutions at various mole fractions of AN/AcAc have been recorded to investigate the interaction of AN with AcAc. In the binary solutions, the intensity of AN stretching bands gets reduced much while that of the AcAc bands suffer minor changes. AN dimers dissociate into monomers even in the binary solution with the AcAc concentration of one fourth of AN concentration. The ν C ≡ N gets red-shifted and remain more or less at the same wavenumber in all the solutions. The nature of shift in AN ν C H 3 bands shows that AN – AcAc non-classical H – bonds are weaker than AN – AN interactions. The red shift in ν C ≡ N is the indication of formation of C ≡ N ⋯ H A c A c C H 3 / O − H H – bonds which are stronger than A N C ≡ N ⋯ H A N C H 3 interactions. Using DFT calculations, the interactions in the 1:1 complexes have been analysed.